Problems Faced by Bank Employees in Implementation of Financial Inclusion Schemes - Kaur, Supreet; Pasricha, J. S. (Indian Journal of Finance, 2019)
It is pertinent to have a financially inclusive system in order to run the engine of growth. Banks being the key stimulators in an economy create an enabling environment in order to run on the pathway to inclusive growth. It is difficult to give form to any of the initiatives if the banks do not mediate. They are the lifeline of a financial system that knits the prevailing gaps by linking the unbanked segment with the vision of financial inclusion. Providing timely and comprehensive financial services and products through a panoply of channels and institutions has always been accorded as a priority by the banks. The Government of India announced three major schemes, that is, Direct Benefit Transfer Scheme, Jan Dhan Yojana, and Atal Pension Yojana in the past specifically designed for targeting industrial workers so as to link them with the financial system. The onus of implementation lies on the shoulders of the bankers, and therefore, it is necessary that there should not be any hurdles in the implementation phase. The purpose of this paper was to analyze the various problems faced by bank employees in implementation of the selected financial inclusion schemes for the industrial workers. For the same, data were gathered from 107 bank officials working in Delhi and NCR using semi-structured personal interviews during the period of March-June 2018. Exploratory factor analysis, cross tabulation, and chi-square test were used for scale purification and data analysis. The current study succeeded in exploring the factors related to issues faced by bankers in implementing the schemes that are defined as predictors of financial inclusion by the government.